Association of Physical Activity Level, Income and Environmental Factors Among Chinese Adults - Dong, Jingjuan; Liu, Wei (Frontiers in Public Health, 2022)
The purpose of this study was to evaluate associations between physical activity level and income and environmental factors among chinese adults. Through the empirical study of the survey data, it is found that: (1) after controlling for the relevant variables, residents' income has a positive impact on residents' participation in physical activities, and the regression coefficient is 0.541 (P < 0.01) (2) In the regression model after adding environmental variables, the regression coefficient of environmental variables increased from 0.401 (P < 0.01) to the highest 1.32 (P < 0.01) (3) Through the comparison of the KHB decomposition method, the intermediary effect of residents' income on environmental factors and participation in physical activities is 0.134 (P < 0.01), and the intermediary effect ratio is 27.01%. Suggestions: first, the government and society should actively provide public goods needed for physical activities to meet the needs of residents for physical activities; second, the government should strengthen the supply of sports facilities in residential areas, speed up the transformation of villages in cities and improve the living conditions in residential areas; third, through legislation to protect residents' income, improving income is not only to give citizens enough sense of security and happiness but also a way to improve residents' participation in physical activities.